KARAKTERISTIK PENDERITA GAGAL JANTUNG YANG DIRAWAT INAP DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2015-2016 - Rosnani Sagala; Fazidah A Siregar; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
ABSTRACT Heart failure is one of the health issues that has been deeply concerned. Based on Riset Kesehatan Dasar 2013,at the age of ≥15, prevalence of heart failure in North Sumatera is equal to prevalence in Indonesia which is 300/100,000 population. In 2015-2016 at Santa Elisabeth Hospital Medan, case fatality rate (CFR)of heart failure is 10.4%.The purpose of this study to know the characteristics of patients with heart failure that hospitalized at Santa Elisabeth Hospital Medan in 2015-2016. This study is descriptive with case series design. Population is all of data patient of heart failure that hospitalized at Santa Elisabeth Hospital Medan in 2015-2016that is 370 people with 192 of themas samples that selected by simple random sampling.The data was analyzed with Chi-Square, Mann-Whitney, and Kruskal Wallis. The result shows that the highest proportion of patients are in >65 years old (41.7%), male (52.6%), Batak Toba(53,6%), Christian (67.7 %), Housewives (29.2%), live out of Medan (50.5%), second stage of heart failure (61.4%), history of hypertension (29,7%), self cost (49.0%), average length of stay 6.01 days (6 days), becoming outpatient (80.2%). There is no significant difference between: age based on sex (p=0.651) andclassification of heart failure (p=0.882), gender based on classification of heart failure (p=0.750), classification of heart failure based onhistory of disease (p=0.554), average length of stay based onclassification of heart failure (p=0.785) and history of disease (p=0.272), classification of heart failure based on condition by going home (p=0.204),history of disease based oncondition by going home (p=0,116). It was recommended to outpatients of heart failureto perform routine checks and to maintain healthty life style to prevent the severity of heart failure. Recommended for hospital complementing the system of medical record. Keywords: Characteristics, Heart Failure, Santa Elisabeth Hospital Medan